2007
DOI: 10.1515/cclm.2007.343
|View full text |Cite
|
Sign up to set email alerts
|

Haptocorrin in humans

Abstract: Our results indicate that haptocorrin is widely distributed also in foetal tissues and suggest analogues to accumulate on haptocorrin in vitamin B(12)-deficient individuals, a result that warrants further studies employing methods directly measuring cobalamins and analogues attached to haptocorrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 49 publications
3
61
1
Order By: Relevance
“…The largest change after 7 days was in sion compared to the RPMI-CPN group after 2 weeks in culture. This finding is consistent with the increase in the gene for the cobalamin-binding protein haptocorrin, a vitamin B 12 carrier (15). Factors with significant secreted VEGF measured after 2 weeks (240%).…”
Section: Resultssupporting
confidence: 80%
“…The largest change after 7 days was in sion compared to the RPMI-CPN group after 2 weeks in culture. This finding is consistent with the increase in the gene for the cobalamin-binding protein haptocorrin, a vitamin B 12 carrier (15). Factors with significant secreted VEGF measured after 2 weeks (240%).…”
Section: Resultssupporting
confidence: 80%
“…These results agree well with our previous attempt to estimate the amounts of analogs attached to HC by calculating holoHC minus HC-Cbl, where HC-Cbl was defined as total Cbl minus holoTC. Using this method, we found that Cbl analogs account for about 40% of all corrinoids on HC in non-Cbldeficient donors, and about 60% of all corrinoid on HC among Cbl-deficient patients (24 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCsat is expected to correlate with MMSE similarly to holoTC, because holoTC-the amount of B 12 available for cellular uptake (11 )-is included in this value. In contrast, B 12 -HC is not directly available to all cells (18,20 ). The strong correlation of B 12 -HC with MMSE is therefore likely to be indirect.…”
Section: Holotc and B 12 -Hc Correlate To Cognitive Impairment And Tomentioning
confidence: 98%